Two new species of Mallocybe from Himalayan forests of Asia - Naseer, Arooj; Khurshid, Rubab; Fan, Yu-Guang; Khalid, Abdul Nasir (Phytotaxa, 2024)
The genus Mallocybe is poorly studied in Asia, with little known species diversity of the genus in Himalayan forests of Pakistan, a hotspot for biodiversity. Based on morphological characters and molecular data, two new species of Mallocybe from Himalayas of Asia are described. One species, Mallocybe himalayana has been collected from Himalayas of China and Azad Jammu & Kashmir, Pakistan. Mallocybe kashmiriana has been described from Himalayas of Azad Jammu and Kashmir, Pakistan. Detailed morphological descriptions, drawings of microstructures for novel taxa are provided. Phylogenetic analyses inferred from internal transcribed spacer (ITS), large subunit (LSU) and second largest subunit of RNA polymerase II (rpb2) sequences show the novelty of these taxa.